Supply Chain Performance Measurement Model: A Literature Review - Saleheen, Ferdoush; Habib, Md. Mamun; Hanafi, Zurina (International Journal of Supply Chain Management, 2018)
Supply chain is being envisaged as an extended enterprise connecting business in different places and facilitating allies to propel competitive advantage in the era of globalization. Substantial research has been undertaken along with literatures on supply chain performance management from cost and non-cost standpoint, strategic, tactical or emphasis on operational aspects; perspectives from commercial as well as financial arenas. In order to gratify customer orders rapidly and efficiently than competitors, supply chain needs to warrant continuous upgradation of its processes and competitive strategies and to apprehend how supply chain contests? it is indispensable to realize the overall performance of the supply chain. However, still many companies miscarry to acquire effective performance measurement tools and techniques to attain integrated Supply Chain Management (SCM). The rationale of this paper is to evaluate the literature on performance measurement for supply chain to apprehend current practices, recognize gaps and advocate future research itineraries. The paper also offers a synopsis and appraisal of the performance measurement used through different supply chain models.